The Key Role of microRNAs in Initiation and Progression of Hepatocellular Carcinoma - Khan, Suliman; Zhang, De-Yu; Zhang, Ji-Yu; Hayat, Mian Khizar; Ren, Jingli; Nasir, Safyan; Fawad, Muhammad; Bai, Qian (Frontiers in Oncology, 2022)
Hepatocellular carcinoma (HCC) is the main type of primary liver malignancy and the fourth leading cause of cancer-related death worldwide. MicroRNAs (miRNAs), a type of non-coding RNA that regulates gene expression mainly on post-transcriptional level has a confirmed and important role in numerous biological process. By regulating specific target genes, miRNA can act as oncogene or tumor suppressor. Recent evidence has indicated that the deregulation of miR-NAs is closely associated with the clinical pathological features of HCC. However, the precise regulatory mechanism of each miRNA and its targets in HCC has yet to be illuminated. This study demonstrates that both oncogenic and tumor suppressive miRNAs are crucial in the formation and development of HCC. miRNAs influence biological behavior including proliferation, invasion, metastasis and apoptosis by targeting critical genes. Here, we summarize current knowledge about the expression profile and function of miRNAs in HCC and discuss the potential for miRNA-based therapy for HCC.